2013
DOI: 10.1111/cxo.12015
|View full text |Cite
|
Sign up to set email alerts
|

Retinal amino acid neurochemistry in health and disease

Abstract: Advances in basic retinal anatomy, genetics, biochemical pathways and neurochemistry have not only provided a better understanding of retinal function but have also allowed us to link basic science to retinal disease. The link with disease allowed measures to be developed that now provide an opportunity to intervene and slow down or even restore sight in previously ‘untreatable’ retinal diseases. One of the critical advances has been the understanding of the retinal amino acid neurotransmitters, related amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 237 publications
(696 reference statements)
0
25
0
Order By: Relevance
“…The collagen content in YFTE would vary with the age of species. However it is well established that glycine is a major amino acid in collagen protein ) According to Kalloniatis et al (2013) glutamate is a major excitatory neurotransmitter in the retina and found to be most abundant amino acid in the eye of vertebrates. Other major amino acids are aspartic acid, alanine and leucine.…”
Section: Amino Acid Profile Of Yellowfin Tuna Eyementioning
confidence: 99%
“…The collagen content in YFTE would vary with the age of species. However it is well established that glycine is a major amino acid in collagen protein ) According to Kalloniatis et al (2013) glutamate is a major excitatory neurotransmitter in the retina and found to be most abundant amino acid in the eye of vertebrates. Other major amino acids are aspartic acid, alanine and leucine.…”
Section: Amino Acid Profile Of Yellowfin Tuna Eyementioning
confidence: 99%
“…Vinpocetine also modulated Müller cell amino acid homeostasis. Altered amino acid metabolism is a hallmark of retinal ischemia and other retinal pathologies (19,20,26,33,42,43,60). In this study, Müller cell glutamate-to-glutamine ratios were elevated following ischemia-reperfusion.…”
Section: Discussionmentioning
confidence: 52%
“…This pathway is closely linked to energy metabolism (reviewed in Ref. 33), and, thus, vinpocetine's actions on glucose availability could alter glutamate metabolism in Müller cells. Additionally, changes in Müller cell glutamate may affect neurons, as retinal neurotransmitters are sourced from Müller cells.…”
Section: Metabolic Effects Of Vinpocetine On Subsequent Metabolic Insmentioning
confidence: 99%
“…Glutamate is a major excitatory amino acid neurotransmitter in the central nervous system of vertebrates and appears to be involved in neuronal transmission in the retina (Massey and Redburn, 1987;Brandst€ atter and Hack, 2001;Yang, 2004;Kalloniatis et al, 2013). In the mammalian retina, glutamate acts in the vertical pathway of visual information, i.e., photoreceptorsebipolar cellseganglion cells.…”
Section: Introductionmentioning
confidence: 99%